The cost of discipleship - Bonhoeffer, Dietrich, 1906-1945. (New York : Touchstone, 1995)
What can the call to discipleship, the adherence to the word of Jesus, mean today to the businessman, the soldier, the laborer, or the aristocrat? What did Jesus mean to say to us? What is his will for us today? Drawing on the Sermon on the Mount, Dietrich Bonhoeffer answers these timeless questions by providing a seminal reading of the dichotomy between "cheap grace" and "costly grace."
[pt]. 1. Grace and discipleship -- 1. Costly grace -- 2. The call to discipleship -- 3. Single-minded obedience -- 4. Discipleship and the cross -- 5. Discipleship and the individual -- [pt]. 2. The sermon on the Mount -- Matthew 5 : of the "extraordinariness" of the Christian life -- 6. The beatitudes -- 7. The visible community -- 8. The righteousness of Christ -- 9. The brother -- 10. Woman -- 11. Truthfulness -- 12. Revenge -- 13. The enemy, the "extraordinary" -- Matthew 6 : of the hidden character of the Christian life -- 14. The hidden righteousness -- 15. The hiddenness of prayer -- 16. The hiddenness of the devout life -- 17. The simplicity of the carefree life -- Matthew 7 : the separation of the disciple community -- 18. The disciple and unbelievers -- 19. The great divide -- 20. The conclusion -- [pt]. 3. The messengers -- 21. The harvest -- 22. The apostles -- 23. The work -- 24. The suffering of the messengers -- 25. The decision -- 26. The fruit -- [pt]. 4. The Church of Jesus Christ and the life of discipleship -- 27. Preliminary questions -- 28. Baptism -- 29. The body of Christ -- 30. The visible community -- 31. The saints -- 32. The image of Christ.
Previously published: New York : Macmillan, 1959.
Includes indexes.
Includes bibliographical references and indexes.
Keywords: Sermon on the mount -- Criticism, interpretation, etc; Christian life -- Bekennende Kirche authors